Tahlῑlu Al-Akhtha' Al-Imlāiyyati Fi tadrῑbāti Al-Lughati Al-'Arabiyyati Lada Talāmῑdzi Ash-Shaffi Ats-tsāmini Fi Madrosati Al-Mutawassithati Al-Islāmiyyati Bi Ma'hadi Al-Ihsan Riau - Siti Masyfufah; Agustiar; Masrun; Hakmi Wahyudi; Mukhamad Hadi Musolin (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
Al Ihsan Boarding School Riau, as an Arabic language educational institution, still faces obstacles, as some eighth-grade students make errors in Imla'. This study aims to identify the types of Imla' errors, the factors causing them, and the proposed solutions. This qualitative research employed a descriptive analysis method, with data collected through observation, interviews, and documentation. The findings reveal several categories of errors: 75 errors (38%) in hamzah washal, 87 errors (25%) in hamzah qatha', 27 errors (21%) in the addition and omission of Hijaiyah letters, and 18 errors (14%) in the transposition of Hijaiyah letters. The causes of these errors include internal factors, such as lack of confidence, low concentration, insufficient independent practice, limited writing habits, incomplete understanding of Imla' rules, and weak mastery of makharijul huruf. External factors involve aspects of the learning system and an unfavorable learning environment. The proposed solutions include providing structured and continuous practice, strengthening students’ understanding of spelling rules, increasing motivation and interest in writing practice, and enhancing the teacher’s role in the learning process. The practical implications suggest that teachers should integrate systematic Imla' exercises and explicit rule instruction into daily learning activities, while schools should support a conducive environment, adequate resources, and regular evaluation to reduce recurring errors and improve students’ Arabic writing proficiency.